Pengaruh Influencer Marketing terhadap Keputusan Pembelian Produk Kecantikan di Kalangan Generasi Z : Literature Review - Fera Anggraini; Mirzam Arqy Ahmadi (Journal of Management and Creative Business, 2025)
The development of digital technology and social media has changed the way beauty products are marketed, especially through influencer marketing which is increasingly popular among Generation Z. This study aims to analyze the influence of influencer marketing on the purchase decision of beauty products among Generation Z through a comprehensive literature study. The method used is literature review by analyzing related research journals published in the period 2019-2024. The results showed that influencer marketing has a significant influence on purchasing decisions, Generation Z uses social media as the main source of beauty product information. Buying decisions seen from influencer credibility, short video content format, authenticity, and interaction with followers are key factors in Generation Z's complex decision-making process, involving research from various sources before making a purchase decision. Sustainability and ethical beauty factors also support important considerations Generation Z prefers products promoted by influencers who care about sustainability issues.